Ultrasound - operative correlation in gallbladder disease - Olivera, Eduardo; Martínez, Ivonne; Caputti, Sonia; Macchi, Daniel; Soto, Martha (Cirugía del Uruguay, 1991)
This prospective study controlled with operative findings evaluates the efficacy of preoperative echography performed at the Hospital de Clínicas in the diagnosis of ga/1-bladder pathology in a series of 40 patients.